Crystalline form of 6-(cyclopropanecarboxamido)-4-((2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)phenyl)amino)-N-(methyl-d3)pyridazine-3-carboxamide

JP2024505063A5Inactive Publication Date: 2025-01-30BRISTOL MYERS SQUIBB CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023545957
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-01-29
Filing Date
2022-01-28
Publication Date
2025-01-30
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

Crystalline form E of 6-(cyclopropanecarboxamido)-4-((2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)phenyl)amino)-N-(methyl-d3)pyridazine-3-carboxamide is disclosed. Form E is a neat crystalline form. Characterization data for form E is disclosed.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention generally relates to crystalline forms of 6-(cyclopropanecarboxamido)-4-((2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)phenyl)amino)-N-(methyl-d3)pyridazine-3-carboxamide. The present invention also generally relates to pharmaceutical compositions comprising the crystalline forms, as well as methods for obtaining such crystalline forms. [Background technology]

[0002] The compound 6-(cyclopropanecarboxamido)-4-((2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)phenyl)amino)-N-(methyl-d3)pyridazine-3-carboxamide has the formula (I): [ka] and is referred to herein as "Compound (I)." Compound (I) is disclosed in commonly assigned U.S. Patent No. RE47,929E. U.S. Patent No. RE47,929E also discloses a method of treatment utilizing Compound (I). Compound (I) is also known as ducravacitinib.

[0003] Compound (I) is a Tyk2 inhibitor currently in clinical trials for the treatment of autoimmune and autoinflammatory diseases, such as psoriasis, psoriatic arthritis, lupus, lupus nephritis, Sjogren's syndrome, inflammatory bowel disease, Crohn's disease, and ankylosing spondylitis.

[0004] In the synthesis of chemical compounds intended for pharmaceutical use, it is necessary to isolate and purify the compound upon completion of the synthesis process and prior to further processing to provide the compound in a pharmaceutical formulation. The isolation and purification steps may be combined or may be separate, sequential steps, and ideally provide the compound as a purified solid, with minimal loss in yield during isolation of the compound from other components of the reaction mixture and / or during purification to remove impurities from an isolated compound sample.

[0005] It would be desirable to provide solid forms of such compounds that can be reproducibly produced from isolation and / or purification steps.

[0006] Additionally, it is desirable to isolate the compound in a solid form that is physically and chemically stable upon storage, including different conditions of temperature and humidity. It would also be advantageous to provide the compound in a solid form that undergoes little loss upon storage and has low moisture absorption.

[0007] It may also be desirable to provide the compound in a solid form that is suitable for further processing, for example, a crystalline form that can be converted to other solid forms (such as amorphous or other crystalline forms).

[0008] As described herein, the crystalline form of Compound (I) surprisingly provides Compound (I) in a solid form that is physically and chemically stable over a range of storage conditions. This crystalline form is also surprisingly suitable for further processing and can be converted into other solid forms. Furthermore, the crystalline form has sufficient solubility in solvents / solutions to allow for the preparation of other solid forms. The present invention relates to these and other important aspects. Summary of the Invention

[0009] The present invention provides crystalline Form E of Compound (I). It should be understood that the name used to characterize a particular form herein (e.g., "Form E") should not be considered limiting with respect to any other substance having similar or identical physical and chemical characteristics, and that the name is merely an identifier that should be interpreted in accordance with the characterization information also presented herein. [Brief explanation of the drawings]

[0010] [Figure 1] FIG. 1 shows the observed powder X-ray diffraction pattern (CuKα, room temperature) of crystalline form E of Compound (I). [Figure 2] FIG. 2 shows a differential scanning calorimetry (DSC) thermogram of crystalline form E of Compound (I). [Figure 3] FIG. 3 shows a thermogravimetric analysis (TGA) thermogram of Form E of Compound (I). [Figure 4] FIG. 4 shows the moisture sorption isotherm of Form E of Compound (I) measured at 25° C. DETAILED DESCRIPTION OF THE INVENTION

[0011] The features and advantages of the present invention may be more readily understood by those skilled in the art upon reading the following detailed description. It should be understood that certain features of the invention that are, for clarity, described above and below in the context of separate embodiments, may also be combined to form a single embodiment. Conversely, various features of the invention that are, for brevity, described in the context of a single embodiment, may also be combined to form subcombinations thereof.

[0012] The designations used herein to characterize particular forms (e.g., "Form E") are merely identifiers that should be interpreted in accordance with the characterization information presented in this specification (or the references cited herein) and should not be limited to exclude any other substances having similar or identical physical and chemical characteristics.

[0013] The definitions set forth herein take precedence over definitions set forth in any patent, patent application, and / or patent application publication incorporated herein by reference.

[0014] All numbers expressing amounts of ingredients, weight percent, temperatures, and the like preceded by the word "about" should be understood as approximations only, in that the stated value may be varied slightly above and below to achieve results substantially similar to the recited number. Accordingly, unless otherwise indicated, numerical parameters preceded by the term "about" are approximations that may vary depending upon the nature of the objective sought to be achieved. At the very least, and not as an attempt to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should at least be construed in light of the number of reported significant digits and by applying ordinary rounding techniques.

[0015] All measurements are subject to experimental error and consistent with the present invention.

[0016] As used herein, "polymorph" refers to crystalline forms that have the same chemical structure but differ in the spatial arrangement of the molecules and / or ions that form the crystals.

[0017] As used herein, "amorphous" refers to a solid form of molecules and / or ions that is not crystalline. Amorphous solids do not exhibit distinct X-ray diffraction patterns with sharp maxima.

[0018] As used herein, "substantially pure," when used in reference to a crystalline form of a compound, means having a crystalline form with a purity of 90% by weight or greater, such as 90, 91, 92, 93, 94, 95, 96, 97, 98, and 99% by weight or greater, and also equivalent to about 100% by weight, based on the weight of the sample or specimen. The remaining material includes other forms of the compound, and / or reaction impurities, and / or processing impurities resulting from its preparation. For example, a crystalline form of Compound (I) may be considered substantially pure in that it has a purity of 90% by weight or greater, as measured by methods now known and generally accepted in the art, wherein the remaining less than 10% by weight of the material includes amorphous and / or other forms of Compound (I), and / or reaction impurities and / or processing impurities.

[0019] As used herein, a powder X-ray diffraction (PXRD) pattern "comprising" multiple peaks selected from a specific group of peaks is intended to include PXRD patterns having additional peaks not included in the specific group of peaks. For example, a PXRD pattern comprising four or more, preferably five or more 2θ values ​​selected from a, b, c, d, e, f, g, and h is intended to include a PXRD pattern having (a) four or more, preferably five or more 2θ values ​​selected from a, b, c, d, e, f, g, and h; and (b) zero or more peaks that are not any of the peaks a, b, c, d, e, f, g, and h.

[0020] The presence of reaction and / or processing impurities may be determined by analytical techniques known in the art, such as, for example, chromatography, nuclear magnetic resonance spectroscopy, mass spectroscopy, and / or infrared spectroscopy.

[0021] As used herein, the unit cell parameter "number of molecules per unit cell" refers to the number of molecules of Compound (I) in a unit cell.

[0022] Forms of Compound (I) are described in WO2018 / 183656 (Form A), WO2019 / 232138 (Form B), and WO2020 / 251911 (Forms C and D). The present invention generally relates to Form E of Compound (I).

[0023] Form E of Compound (I) In some embodiments, Compound (I) is provided as a crystalline material comprising Form E. Crystalline Form E of Compound (I) is a neat crystalline form.

[0024] In certain embodiments, crystalline form E of compound (I) has the following structure: Cell Dimensions: a=10.41±0.10Å b=12.65±0.10Å c=15.70±0.10Å α=90.0° β=103.5±1.0° γ=90.0° Space group: P21 / n Number of molecules per unit cell (Z): 4 Unit cell volume = 2011±20Å 3 Density (calculated value) = 1.406 g / cm 3 is characterized by unit cell parameters approximately equal to Here, the unit cell parameters of Form E of Compound (I) are measured at a temperature of about 100K. [Table 1]

[0025] In some embodiments, crystalline Form E of Compound (I) is characterized by a powder X-ray diffraction (PXRD) pattern (CuKα) comprising two or more 2θ values ​​(in degrees) selected from 9.0±0.2, 11.3±0.2, 15.2±0.2, and 21.1±0.2, wherein the PXRD pattern of Form E is measured at room temperature.

[0026] In certain embodiments, crystalline Form E of Compound (I) is characterized by a powder X-ray diffraction pattern (CuKα) comprising 2θ values ​​(in degrees) at 9.0±0.2 and 11.3±0.2, wherein the PXRD pattern of said Form E is measured at room temperature.

[0027] In a further embodiment, crystalline Form E of Compound (I) is characterized by a powder X-ray diffraction pattern (CuKα) comprising 2θ values ​​(in degrees) at 9.0±0.2, 11.3±0.2, 15.2±0.2, and 21.1±0.2, wherein the PXRD pattern of said Form E is measured at room temperature.

[0028] In certain embodiments, crystalline Form E of Compound (I) is characterized by (i) a powder X-ray diffraction pattern (CuKα) comprising 2θ degrees at 9.0±0.2 and 11.3±0.2, wherein the PXRD pattern of Form E is measured at room temperature; and (ii) an endotherm having a peak maximum in the range of approximately 249° C. to 253° C. In further embodiments, the endothermic peak maximum is about 251° C. It should be understood that in some cases, an endothermic event may not be detected.

[0029] In certain embodiments, crystalline Form E of Compound (I) is characterized by (i) a powder X-ray diffraction pattern (CuKα) comprising 2θ values ​​(in degrees) at 9.0±0.2, 11.3±0.2, 15.2±0.2, and 21.1±0.2, wherein the PXRD pattern of Form E is measured at room temperature; and (ii) an endotherm having a peak maximum in the range of approximately 249° C. to 253° C. In further embodiments, the endothermic peak maximum is about 251° C.

[0030] In certain embodiments, crystalline Form E of Compound (I) is characterized by an observed powder X-ray diffraction pattern substantially as shown in FIG.

[0031] In some embodiments, crystalline Form E of Compound (I) is characterized by an endothermic peak maximum in the range of approximately 249° C. to 253° C. In further embodiments, the endothermic peak maximum is about 251° C.

[0032] In some embodiments, crystalline Form E of Compound (I) is characterized by a differential scanning calorimetry (DSC) thermogram substantially in agreement with the thermogram depicted in FIG.

[0033] In certain embodiments, crystalline Form E of Compound (I) is characterized by (i) a powder X-ray diffraction pattern (CuKα), measured at room temperature, comprising 2θ values ​​(in degrees) at 9.0±0.2 and 11.3±0.2; and (ii) a differential scanning calorimetry (DSC) thermogram substantially in agreement with the thermogram depicted in FIG. 2.

[0034] In some embodiments, crystalline form E of Compound (I) is characterized by a thermogravimetric analysis (TGA) thermogram having a weight loss of less than 0.1% when heated to a temperature of about 150° C. In certain embodiments, crystalline form E of Compound (I) is characterized by a thermogravimetric analysis (TGA) thermogram having a weight loss of less than 0.1% when heated to a temperature of about 175° C. In further embodiments, crystalline form E of Compound (I) is characterized by a thermogravimetric analysis (TGA) thermogram exhibiting a weight loss of less than 0.5% at about 200° C.

[0035] In certain embodiments, crystalline Form E of Compound (I) exhibits a thermogravimetric analysis (TGA) thermogram substantially as shown in FIG.

[0036] In certain embodiments, crystalline Form E of Compound (I) exhibits a moisture sorption isotherm substantially as shown in FIG.

[0037] In some embodiments, Form E of Compound (I) is substantially pure. For example, Form E of Compound (I) may be present in a sample at 90% or greater, 95% or greater, or 99% or greater purity by weight, with the remainder of the material comprising other forms of the compound and / or reaction and / or processing impurities.

[0038] In certain embodiments, the crystalline form of Compound (I) consists essentially of Form E. For such embodiments, crystalline Compound (I) may comprise at least about 90% by weight, preferably at least about 95% by weight, and more preferably at least about 99% by weight, of crystalline Form E, based on the weight of Compound (I).

[0039] Certain embodiments also provide a composition comprising 6-(cyclopropanecarboxamido)-4-((2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)phenyl)amino)-N-(methyl-d3)pyridazine-3-carboxamide, wherein at least 95%, preferably at least 97%, and more preferably at least 99% by weight of the 6-(cyclopropanecarboxamido)-4-((2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)phenyl)amino)-N-(methyl-d3)pyridazine-3-carboxamide is crystalline form E.

[0040] In a further embodiment, there is provided a pharmaceutical composition comprising Form E of Compound (I) and at least one pharmaceutically acceptable carrier and / or diluent.

[0041] In certain embodiments, the pharmaceutical composition comprises substantially pure Form E of Compound (I) and at least one pharmaceutically acceptable carrier and / or diluent.

[0042] In certain embodiments, Form E of Compound (I) is combined with at least one pharmaceutically acceptable carrier and / or diluent to provide at least one pharmaceutical composition.

[0043] In some embodiments, the pharmaceutical composition comprises Form E of Compound (I) and other solid forms of Compound (I). Such other solid forms can be, for example, other crystalline forms (e.g., Form A) and / or amorphous Compound (I).

[0044] Crystalline forms may be prepared by a variety of methods, such as, for example, crystallization or recrystallization from a suitable solvent, sublimation, growth from the melt, solid-state phase transformation from another phase, crystallization from supercritical fluids, and jet spray. Techniques for crystallizing or recrystallizing crystalline forms from solvent mixtures include, for example, evaporation of the solvent, reducing the temperature of the solvent mixture, seeding a supersaturated solvent mixture with molecules and / or salts, freeze-drying the solvent mixture, and adding antisolvents (countersolvents) to the solvent mixture. High-throughput crystallization techniques may be used to prepare crystalline forms, including polymorphs.

[0045] Drug crystals, including polymorphism, preparation methods, and characteristics of drug crystals are discussed in Solid-State Chemistry of Drugs, by SR Byrn, RR Pfeiffer, and JG Stowell, 2 nd Edition, SSCI, West Lafayette, Indiana (1999).

[0046] For solvent-based crystallization techniques, the choice of solvent generally depends on one or more factors, such as the solubility of the compound, the crystallization technique, and the vapor pressure of the solvent. Solvents may be used in combination; for example, a compound may be solubilized in a first solvent to obtain a solution, and then an anti-solvent may be added to reduce the solubility of the compound in the solution, resulting in the formation of crystals. An anti-solvent is a solvent in which the compound has low solubility.

[0047] In one method of preparing crystals, a compound is suspended and / or stirred in a suitable solvent to obtain a slurry, which may be heated to promote dissolution. As used herein, the term "slurry" refers to a saturated solution of a compound, which may also contain additional amounts of compound to obtain a heterogeneous mixture of compound and solvent at a given temperature.

[0048] Seed crystals may be added to any crystallization mixture to promote crystallization. Seeding may be used to control the growth of a particular polymorph or to control the particle size distribution of the crystalline product. Therefore, as described, for example, in "Programmed Cooling of Batch Crystallizers," J. W. Mullin and J. Nyvlt, Chemical Engineering Science, 1971, 26, 369-377, the calculation of the amount of seeds required depends on the size of the available seeds and the desired size of the average product particle. Generally, small-sized seeds are required to effectively control the growth of crystals within a batch. Small-sized seeds may be created by sieving, grinding, or atomizing larger crystals or by microcrystallizing a solution. Care must be taken when grinding or atomizing crystals to avoid any change in crystallinity from the desired crystalline form (i.e., to amorphous or another polymorph).

[0049] The cooled crystallization mixture may be vacuum filtered, and the isolated solid may be washed with a suitable solvent, such as a cold recrystallization solvent, and dried under a nitrogen purge to obtain the desired crystalline form. The isolated solid may be analyzed by one or more suitable spectroscopic or analytical techniques, such as solid-state nuclear magnetic resonance, differential scanning calorimetry, X-ray powder diffraction, or the like, to assess the formation of the desired crystalline form of the product. The resulting crystalline form is generally produced in an isolated yield of about 70% by weight or greater, preferably 90% by weight or greater, based on the weight of the compound initially used in the crystallization procedure. If necessary, the product may be co-milled or crushed by passing it through a mesh screen.

[0050] The crystalline form may be prepared directly from the reaction medium of the final process for preparing Compound (I). Such preparation may be achieved, for example, by using a solvent or mixture of solvents that will crystallize Compound (I) in the final process step. Alternatively, the crystalline form may be obtained by distillation or solvent addition techniques. Suitable solvents for this purpose include, for example, the nonpolar and polar solvents mentioned above, for example, protic polar solvents such as alcohols, and aprotic polar solvents such as ketones.

[0051] The presence of more than one polymorph in a sample may be determined by techniques such as powder X-ray diffraction (PXRD) or solid-state nuclear magnetic resonance spectroscopy (ssNMR). For example, the presence of extra peaks in a comparison of an experimentally measured PXRD pattern with a simulated PXRD pattern may indicate the presence of more than one polymorph in a sample. Simulated PXRD may be calculated from single crystal X-ray data. See Smith, DK, "A FORTRAN Program for Calculating X-Ray Powder Diffraction Patterns," Lawrence Radiation Laboratory, Livermore, California, UCRL-7196 (April 1963).

[0052] Form E of Compound (I) may be characterized using various techniques whose operation is well known to those skilled in the art. Form E may be characterized and distinguished using single crystal X-ray diffraction, which is based on unit cell measurements of a single crystal at a fixed analysis temperature. A detailed description of the unit cell is provided in Stout & Jensen, X-Ray Structure Determination: A Practical Guide, Macmillan Co., New York (1968), Chapter 3, which is incorporated herein by reference. Alternatively, the unique atomic arrangement in spatial relationship within the crystal lattice may be characterized according to the observed fractional atomic coordinates. Another method for characterizing the crystal structure is by powder X-ray diffraction analysis, in which a diffraction profile is compared with a simulated profile representing the pure powder material, both performed at the same analysis temperature, and the measurements of the target form are characterized as a series of 2θ values ​​(e.g., 2, 3, 4, or more).

[0053] Other methods for characterizing forms may be used, including solid-state nuclear magnetic resonance (ssNMR), differential scanning calorimetry (DSC), thermography, and visual examination of crystalline or amorphous forms. Two or more of these parameters may also be used in combination to characterize the form of interest.

[0054] usefulness Crystalline Form E of Compound (I) can be used to isolate Compound (I) from other components upon completion of the synthesis process; and / or to purify Compound (I) by one or a series of crystallization steps. The isolation and purification steps can be combined or performed as separate processing steps. Crystalline Form E can also be used to create other solid forms of Compound (I) (e.g., Form A, described in WO 2018 / 183656) and / or amorphous Compound (I). In certain embodiments, a method for preparing amorphous Compound (I) comprises preparing crystalline Form E, wherein crystalline Form E is characterized as described herein. In further embodiments, such amorphous Compound (I) is then used to create a dosage form for clinical use (e.g., a dosage form comprising a solid dispersion of amorphous Compound (I)).

[0055] Crystalline Form E of Compound (I) may be used alone or in combination with other forms of Compound (I) and / or formulated with one or more excipients or other active ingredients to make pharmaceutical compositions. [Example]

[0056] The present invention is further described by the following examples, which are preferred embodiments of the invention. Unless otherwise specified, all temperatures are in degrees Celsius (°C). It should be understood that these examples are illustrative rather than limiting, and that other embodiments may exist that are within the spirit and scope of the invention.

[0057] For ease of reference, the following abbreviations may be used herein: [Table 2]

[0058] Example 1: Preparation of crystalline form E of compound (I) Approximately 33 mg of Compound (I) was dissolved in 0.16 mL of NMP at 90° C. in a 1 mL vial. The vial was placed in a reactor block at 100° C., and 0.8 mL of 1,4-dioxane was added. The vial was continuously stirred overnight at 80° C. The vial was then cooled to ambient temperature and subsequently stirred for 2 days. A sample isolated for PXRD showed the pattern of Form E.

[0059] Example 2: Preparation of crystalline form E of compound (I) 200 mg of Compound (I) was placed in 0.8 mL of NMP and then dissolved by heating in a block set at 90°C. After cooling to room temperature, 3 mL of 1,4 dioxane was added. Seeding was performed using the remainder of the slurry from the previous experiment (Example 1). An additional 4 mL of dioxane was added, and the mixture was stirred overnight at ambient temperature, resulting in the formation of crystals. The crystals were isolated by filtration, washed with excess MTBE (to dehydrate the NMP / dioxane), and dried overnight at ambient temperature under 25 inches of vacuum. The dried powder exhibited the PXRD pattern of Form E.

[0060] Example 3: Preparation of crystalline form E of compound (I) Approximately 2 g of Compound (I) was dissolved in 36 g of 80:20 wt% 1-BuOH:water at 75°C for approximately 20-30 minutes until a clear solution was obtained. The solution was hot filtered into a preheated flask, then the flask was capped and placed in a freezer overnight, resulting in a white precipitate (thick suspension) that had consumed all of the liquid phase. The suspension was stored in the freezer for approximately 4 months. The thick suspension was then transferred onto filter paper for vacuum filtration. The resulting wet cake was washed twice with 10 mL of 70:30 wt% acetone:water. Approximately 5.78 g of the wet solid was then suspended in 21 mL of 70:30 wt% acetone:water. The resulting suspension was subjected to three temperature cycles: 5-45-5°C; two cycles: 5-35-5°C; and one cycle: 10-35-10°C, followed by a final hold at 10°C for 6 hours. The solids from the suspension were isolated by vacuum filtration and washed twice with 5 mL of 70:30 wt% acetone:water. The solids were exposed to 84% RH for 1 day. A small portion was analyzed by PXRD, which was consistent with Form E. The sample was then dried under vacuum at approximately 42°C for 1 day and reanalyzed. The solids were again consistent with Form E.

[0061] 6-(Cyclopropanecarboxamido)-4-((2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)phenyl)amino)-N-(methyl-d 3 ) Synthesis of pyridazine-3-carboxamide Step 1: Preparation of Compound 2 [ka] Toluene (0.26 kg), sulfolane (3.4 kg), compound 1 (1.0 kg), and POCl (2.7 kg) were charged into a glass-lined reactor. The crude was cooled to 0°C. Triethylamine (0.89 kg) was charged, and the resulting crude mixture was heated to 65°C and aged until the reaction was complete. The reaction mass was cooled to 5°C.

[0062] A separate reactor was charged with water (7.5 kg) and cooled to 5°C. The reaction mass was slowly added to the aqueous solution, maintaining the internal temperature below 5°C. Additional water (0.5 kg) was used to rinse the reactor and facilitate transfer. The resulting mixture was stirred at 5°C for 3 hours and then extracted three times with MTBE (3 x 4.5 kg). The combined organic layers were washed successively with a pH 7 aqueous buffer solution (5.0 L / kg, 15 wt% KH2PO4 / K2HPO4) and water (2.5 kg). The crude material was vacuum distilled to a total volume of approximately 3 L / kg. ACN (2 x 6.3 kg) was added, followed by further distillation to approximately 3 L / kg. The crude material was cooled to 20°C to give compound 2 as a 30-36 wt% solution in 90-95% yield.

[0063] Step 2: Preparation of Compound 3 [ka] ACN (2.7 kg), lithium bromide (1.18 kg), and water (0.65 kg) were charged to a glass-lined reactor at 25°C. The crude solution of compound 2 (the limiting reagent) prepared above was added, followed by DIPEA (1.82 kg). The resulting slurry was stirred at 25°C until the reaction was complete. The product was isolated by filtration. The crude solid was washed with ACN (1.6 kg). The cake was dried under vacuum at 45°C. Compound 3 was isolated in 98 AP and 83% yield.

[0064] Step 3: Preparation of Compound 8 [ka] Water (6.0 kg, 6.0 L / kg) and compound 7 (1.0 kg) were charged to a glass-lined reactor at 25°C. Anhydrous zinc acetate (1.08 kg, 1.0 equiv) was added, followed by compound 3 (1.28 kg, 1.20 equiv). The reactor line was rinsed with 2-propanol (0.79 kg, 1.0 L / kg) and water (1.50 kg, 1.50 L / kg). The resulting homogeneous solution was heated to 65°C and aged until the reaction was complete. Water (7.0 kg, 7.0 L / kg) was added, and the crude mixture was cooled to 20°C and aged for 30 minutes. The product was isolated by filtration. The crude solid was washed successively with water (6.0 kg, 6.0 L / kg), water (6.0 kg, 6.0 L / kg), THF (5.3 kg, 6.0 L / kg), and THF (5.3 kg, 6.0 L / kg). The cake was dried under vacuum at 70 °C. Compound 8 was isolated in 98 AP and 94% yield.

[0065] Step 4: Preparation of Compound 9 [ka] Another glass-lined reactor was flushed with nitrogen. Toluene (0.87 kg, 1.0 L / kg) and MeCN (0.79 kg, 1.0 L / kg) were added, followed by (2R)-1-[(1R)-1-[bis(1,1-dimethylethyl)phosphino]ethyl]-2-(dicyclohexylphosphino)ferrocene (Josiphos SL-009-01) (14.1 g, 1.0 mol%) and palladium acetate (2.9 g, 0.5 mol%). The reactor lines were rinsed with toluene (0.43 kg, 0.5 L / kg). The resulting preformed catalyst solution was kept under nitrogen until further use.

[0066] At 20°C, toluene (3.46 kg, 4.0 L / kg) and ACN (1.57 kg, 2.0 L / kg) were charged to a nitrogen-flushed, glass-lined reactor. Compound 8 (1.00 kg) was added, followed by DBU (0.39 kg, 1.00 equiv). The reactor lines were rinsed with toluene (0.43 kg, 0.5 L / kg). Compound 10 (0.54 kg, 2.5 equiv) and K2CO3 (325 mesh grade, 0.70 kg, 2.0 equiv) were added to the reaction mixture, followed by toluene (1.30 kg, 1.5 L / kg) and ACN (0.79 kg, 1.0 L / kg). The pre-formed catalyst solution was transferred into the reaction mixture, which was then heated to 75°C and stirred until the reaction was complete.

[0067] The reaction crude was cooled to 20°C. Aqueous acetic acid (50% by volume, 4.0 kg, 4.0 L / kg) was slowly charged over 1 hour. Glacial acetic acid (10.5 kg, 10.0 L / kg) was then added. The resulting homogeneous solution was washed twice with heptane (2 x 3.42 kg, 2 x 5.0 L / kg). The bottom aqueous layer was collected and transferred to a clean reactor. Water (5.0 kg, 5.0 L / kg) was added, followed by compound 9 seeds (0.01 kg, 1.0 wt%). The slurry was aged for 2 hours at 20°C. Additional water (2.0 kg, 2.0 L / kg) was added, and the slurry was further aged for 6 hours. The product was isolated by filtration. The crude cake was washed with aqueous ACN (50% by volume, 4.5 kg, 5.0 L / kg) followed by ACN (3.9 kg, 5.0 L / kg). The cake was dried under vacuum at 65° C. Compound 9 was isolated in 98.5 AP and 84% yield.

[0068] Step 5: Preparation of Compound (I) [ka] NMP (2.06 kg, 2.0 L / kg) and ACN (0.78 kg, 1.0 L / kg) were placed in a glass-lined reactor and stirred at 20°C. N-methylimidazole (0.13 kg, 0.7 equiv.), compound 13 (0.17 kg, 1.2 equiv.), and compound 9 (1.00 kg) were added to the reaction mixture. The mixture was heated to 65°C and aged until homogeneous. HOBt 20% wet (0.17 kg, 0.5 eq) was then added to the reaction mixture, followed by EDC HCl (0.54 kg, 1.4 eq). The reactor was rinsed with ACN (0.78 kg, 1.0 L / kg), and the resulting mixture was aged at 65°C until the reaction was complete. The reaction was quenched with charged water (1.0 kg, 1 L / kg) and then diluted with ACN (3.0 kg, 3 L / kg). The reaction mixture was aged at 65°C for 1 hour, then cooled to 0°C and aged for an additional 12 hours at 0°C. The product was isolated by filtration. The wet cake was washed with 2:1 water:ACN (2.8 kg, 3 L / kg) and then with ACN (2.4 kg, 3 L / kg) before drying under full vacuum at 65°C. Compound (I) was isolated in >99.5% purity and 91% yield.

[0069] NMP (6.2 kg, 6.0 L / kg) and Compound (I) (1.0 kg) were charged to a glass-lined reactor. The batch was heated to 70°C, forming a pale yellow solution, which was then passed through a polish filter and transferred to a clean container at 70°C. 2-Propanol (2.4 kg, 3 L / kg) was added, followed by Compound I seeds (0.005 kg, 0.005 kg / kg). After aging for 1 hour, additional 2-propanol (4.8 kg, 6 L / kg) was charged over 2 hours (3 L / kg / hr). The slurry was aged for 1 hour at 70°C, slowly cooled to 0°C, and aged for an additional 12 hours at 0°C. The product was isolated by filtration. The wet cake was washed with 2-propanol (2 x 3.1 kg, 2 x 4 L / kg) and then dried at 65°C under full vacuum. Compound (I) was isolated in >99.9% purity and 83% yield.

[0070] Preparation of Compound 7 Step 1: Preparation of N-methyl-N-formylhydrazine [ka] A glass-lined reactor was charged with methanol (1.6 kg / kg, 2.0 L / kg) and methylhydrazine (1 kg) at 0°C. Methyl formate (0.57 kg / kg, 1.1 equiv) was added dropwise. The crude material was warmed to 20°C and aged for an additional 6 hours. The crude material was vacuum distilled to a total volume of approximately 0.5 L / kg. Five put / take distillations with 2-MeTHF (5 x 3.6 kg / kg) were performed for azeotropic drying. The crude material was cooled to 20°C. N-methyl-N-formylhydrazine was isolated as an 89-90 wt% solution in 89-91% yield.

[0071] Step 2: Preparation of Compound 5 [ka] A glass-lined reactor was charged with potassium tert-butoxide (1.5 kg / kg, 2.4 equiv) and THF (12.2 kg / kg) at 0°C. A mixture of compound 4 (1.0 kg), N-methyl-N-formylhydrazine (1.0 kg / kg, 2.30 equiv), and THF (5.3 kg / kg, 6.0 L / kg) was slowly added. The reactor lines were rinsed with THF (0.5 kg / kg). The reaction crude was aged at 0°C until the reaction was complete. Water (5.0 kg / kg) was added, and the resulting mixture was aged at 0°C for 30 minutes, heated to 40°C, and aged for an additional 30 minutes. The layers were separated, and the aqueous layer was discarded. The organic layer was washed with brine (15 wt%, 5.7 kg / kg) and then vacuum distilled to a total volume of approximately 5 L / kg. Azeotropic drying was performed four times with ethyl acetate (4 x 10 L / kg). The crude was cooled to 20 °C. Sulfuric acid (0.66 kg / kg, 1.10 equiv.) was added and the slurry was stirred for 2-3 hours. The product was isolated by filtration. The cake was washed successively with ethyl acetate (2 x 6.5 L / kg) and heptane (8 L / kg) and dried under vacuum at 45 °C. Compound 5 was isolated in 99 AP and 83% yield.

[0072] Step 3: Preparation of Compound 6 [ka] Concentrated sulfuric acid (4.5 kg / kg) and compound 5 (1.0 kg) were placed in a glass-lined reactor at 0-5°C. Nitric acid (68 wt%, 0.35 kg / kg, 1.2 equiv) was added dropwise. The mixture was stirred at 0-5°C until the reaction was complete.

[0073] In a separate reactor, water (12 kg / kg) and methanol (6.5 kg / kg, 8.3 L / kg) were thoroughly mixed at 20°C. The nitrated crude product was slowly transferred to the methanol-water mixture. The reactor lines were rinsed with methanol (0.5 kg / kg). The crude product was heated to 40-45°C. Aqueous ammonium hydroxide solution (25 wt%, 7.4 kg / kg) was slowly added. The resulting slurry was cooled to 20°C and stirred for 3 hours. The product was isolated by filtration. The cake was washed with water (2 x 6 L / kg) and dried under vacuum at 45°C. Compound 6 was isolated with 99 AP and 95% yield.

[0074] Step 4: Preparation of Compound 7 [ka] Methanol (8.0 kg / kg) and compound 6 (1.0 kg) were placed in a nitrogen-flushed high-pressure reactor. Sodium bicarbonate (0.6 kg / kg, 2.0 equiv.) and Pd / C (10% loading, 50% wet, 0.02 kg / kg) were added while carefully excluding oxygen. The reactor was pressurized with hydrogen (41-46 psi), and the reaction mixture was aged at 20°C for 6 hours, then heated to 45°C and aged until the reaction was complete. The reactor was flushed with nitrogen, and the crude reaction mixture was filtered to remove the Pd / C. Methanol (5 kg / kg) was used to facilitate transfer. The combined filtrate was vacuum distilled to a total volume of approximately 2.5 L / kg. Water (10 kg / kg) was added, and the crude product was vacuum distilled to a total volume of approximately 2.5 L / kg. The crude product was heated to 70°C. Brine (25 wt%, 9.0 kg / kg) was added and the resulting crude was stirred for 6 hours at 70°C. After cooling to 0°C, the crude was aged for an additional 6 hours. The product was isolated by filtration. The cake was washed with brine (pre-cooled to 0°C, 25 wt%, 2.0 kg / kg) and dried under vacuum at 45°C. Compound 7 was isolated with 99 AP and 88% yield.

[0075] Preparation of Compound 13 Step 1: Preparation of Compound 11 and Compound 12 [ka] A nitrogen-flushed, glass-lined reactor was charged with water (16.3 L / kg) and sodium hydroxide (3.3 kg, 3.0 equiv). The mixture was aged until the sodium hydroxide was completely dissolved. The crude material was cooled to 0°C. d4-methanol (1.0 kg) and THF (4.5 L / kg) were charged. A solution of TsCl (6.3 kg, 1.2 equiv) in THF (6.3 kg, 7.1 L / kg) was added over 2 hours. The crude material was stirred at 0°C until the reaction was complete. The batch was warmed to 20°C. A liquid separation was performed. The collected organic layer was diluted with MTBE (4.0 kg, 5.4 L / kg) and washed twice with brine (25 wt%, 4.0 kg, followed by 12 kg). The organic layer was vacuum distilled to a total volume of approximately 10 L / kg. Two distillations with ACN (2 × 10 L / kg) were performed for azeotropic drying. The crude was cooled to 20°C. ACN (10.0 kg, 12.8 L / kg) and NaN(CHO)2 (3.3 kg, 1.2 equiv.) were added. The crude was heated to 65°C and stirred until the reaction was complete. After cooling to 5°C, the mixture was filtered and the crude cake was washed twice with ACN (2 x 2.5 kg, 2 x 3.2 L / kg). The combined filtrate was vacuum distilled to a total volume of approximately 3 L / kg. The crude was cooled to 20°C. Compound 12 was isolated as an 80-85 wt% oil in 60-70% yield.

[0076] Step 2: Preparation of compound 13 [ka] A glass-lined reactor was charged with 12 (1.0 kg) and methanol (3.9 kg, 5.0 L / kg) at 20°C. A solution of HCl in IPA (5-6 Normal, 4.5 kg, 1.5 equiv) was added. The resulting mixture was heated to 50°C and stirred until the reaction was complete. THF (10 kg, 11.2 L / kg) was added slowly, and the crude was cooled to 0°C over 2 hours to give a slurry. The product was isolated by filtration. The cake was washed with THF (3.7 kg, 4.1 L / kg) and dried under vacuum at 45°C. 13 was isolated in 80% yield.

[0077] Recrystallization of Compound 13 (Optional): Methanol (5.6 kg, 8.3 L / kg) and compound 13 (1.0 kg) were placed in a glass-lined reactor. DBU (0.1 kg) was added slowly. The crude was stirred for 1 hour. THF (12.4 kg, 13.9 L / kg) was added slowly, and the resulting slurry was aged for 2 hours. The product was isolated by filtration. The cake was washed with THF (2.6 kg, 2.9 L / kg) and dried under vacuum at 45°C. Compound 13 was isolated in 60% yield (first crop). The mother liquor was vacuum distilled to a total volume of approximately 1 L / kg. The solution was concentrated to approximately 1 L / kg by distillation twice with methanol (2 x 2.8 kg, 2 x 3.6 L / kg). The crude was cooled to 20°C. THF (4.8 kg, 5.4 L / kg) was added, and the resulting slurry was aged for 2 hours. The product was isolated by filtration. The cake was washed with THF (1.0 kg) and dried under vacuum at 45° C. Compound 13 was isolated in 25% yield (2nd crop).

[0078] 1. Single Crystal X-ray Measurement Single crystal X-ray data were collected using a Bruker D8 Venture diffractometer equipped with a Photon III detector and a IμS microfocus X-ray source of monochromated Cu Kα radiation. The single crystal was at 100 K during data collection.

[0079] Indexing and processing of the measured intensity data was performed with the APEX3 program suite (Bruker AXS, Inc., 5465 East Cheryl Parkway, Madison, WI 53711 USA).

[0080] The final unit cell parameters were determined using the full data set. The structure was solved by direct methods and refined by full-matrix least-squares using the SHELXTL software package (G.M. Sheldrick, SHELXTL v6.14, Bruker AXS, Madison, WI USA). The refinement of the structure was performed using the Σw(|F o |-|Fc |) 2 This involves minimizing the function defined by, where w is an appropriate weighting factor based on the error in the observed intensity, and F o is the measured reflection-based structure factor, and F c is the calculated reflection-based structure factor. The agreement between the refined crystal structure model and the experimental X-ray diffraction data is given by the residual factor R = Σ||F o |-|F c || / Σ|F o | and wR = [Σw(|F o |-|F c |) 2 / Σw|F o |] 1 / 2 The difference Fourier maps were examined at all stages of the refinement. All non-hydrogen atoms were refined using anisotropic thermal displacement parameters. Hydrogen and deuterium atoms on carbon atoms were introduced using idealized configurations with anisotropic temperature factors and included in the structure factor calculations using fixed parameters. Hydrogen atoms on heteroatoms were positioned from the residual electron density and refined freely using isotropic displacement parameters.

[0081] 2. Powder X-ray Diffraction XRD data were collected using a Bruker D8 Discover DaVinci with an XYZ Stage. The IμS X-ray generator was operated at 50 kV and 1 mA with a Cu target (CuKα radiation). The incident beam optics included a Montel mirror with a 0.3 mm collimator. Photons were counted using an Eiger2 R 500K Detector in 2D, 2θ optimized mode. The sample-to-detector distance was set to 140 mm. Samples were run for 100 seconds in transmission, snapshot mode, with the incident beam at 0° and the detector at 17.5°.

[0082] 3. Differential Scanning Calorimetry Differential scanning calorimetry (DSC) experiments were performed using a TA Instrument model Q2000. Samples (approximately 1–10 mg) were weighed into aluminum pans, and the weight was recorded to the nearest hundredth of a milligram before transferring the samples to the DSC. The instrument was purged with nitrogen gas at 50 mL / min. Data were collected between room temperature and 300 °C at a heating rate of 10 °C / min. DSC plots were generated with the endothermic peak pointing downward.

[0083] 4.Thermogravimetric analysis Thermogravimetric analysis (TGA) experiments were performed using a TA Instrument-model Q5000. Samples (approximately 10-30 mg) were placed in pre-tarred platinum pans. The instrument measured and recorded the sample weight accurately to the thousandth of a milligram. The furnace was purged with nitrogen gas at 25 mL / min. Data were collected between room temperature and 300 °C at a heating rate of 10 °C / min.

[0084] 5. Moisture Sorption Isotherm Moisture sorption isotherms were collected on a TA Instruments VTI-SA+ Vapor Sorption Analyzer using approximately 10 mg of sample. Samples were dried at 60°C until a loss rate of 0.005 wt% / min was obtained for 10 minutes. Samples were tested at 25°C and 4 or 5, 15, 25, 35, 45, 50, 65, 75, 85, and 95% RH (relative humidity). Equilibrium at each RH was achieved when a rate of 0.01 wt% / min was achieved for 35 minutes or when a maximum value of 600 minutes was reached.

Claims

1. 6-(cyclopropanecarboxamido)-4-((2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)phenyl)amino)-N-(methyl-d 3 ) Crystalline form E of pyridazine-3-carboxamide.

2. The following (i) to (iv): (i) the value of: a=10.41±0.10Å b=12.65±0.10Å c=15.70±0.10Å α=90.0° β=103.5±1.0° γ=90.0° Space group: P2 1 / n Number of molecules per unit cell (Z): 4 Unit cell parameters substantially equal to wherein said unit cell parameters are measured at a temperature of about 100K; (ii) a powder X-ray diffraction (PXRD) pattern (CuKα) comprising two or more 2θ values ​​(in degrees) selected from 9.0±0.2, 11.3±0.2, 15.2±0.2, and 21.1±0.2, wherein said PXRD pattern is measured at room temperature; (iii) an observed powder X-ray diffraction (PXRD) pattern substantially as shown in FIG. 1, wherein said PXRD pattern is measured at room temperature; (iv) an endotherm having a peak maximum within the range of about 249° C. to about 253° C. The crystalline form of claim 1, characterized by at least one of:

3. 2. The crystalline form of claim 1, characterized by a powder X-ray diffraction (PXRD) pattern (CuKα) comprising three or more 2θ values ​​(in degrees) selected from 9.0±0.2, 11.3±0.2, 15.2±0.2, and 21.1±0.2, wherein the PXRD pattern of the crystalline form is measured at room temperature.

4. 2. The crystalline form of claim 1, characterized by a powder X-ray diffraction (PXRD) pattern (CuKα) comprising 2θ values ​​(in degrees) at 9.0±0.2, 11.3±0.2, 15.2±0.2, and 21.1±0.2, wherein the PXRD pattern of the crystalline form is measured at room temperature.

5. 2. The crystalline form of claim 1, characterized by: (i) a powder X-ray diffraction pattern (CuKα) measured at room temperature comprising 2θ values ​​(in degrees) at 9.0±0.2 and 11.3±0.2; and (ii) an endotherm having a peak maximum within the range of about 249° C. to about 253° C.

6. 2. The crystalline form of claim 1, characterized by: (i) a powder X-ray diffraction pattern (CuKα) measured at room temperature comprising 2θ values ​​(in degrees) at 9.0±0.2, 11.3±0.2, 15.2±0.2, and 21.1±0.2; and (ii) an endotherm having a peak maximum in the range of about 249° C. to about 253° C.

7. 2. The crystalline form of claim 1, characterized by: (i) a powder X-ray diffraction pattern (CuKα) measured at room temperature comprising 2θ values ​​(in degrees) at 9.0±0.2 and 11.3±0.2; and (ii) a differential scanning calorimetry (DSC) thermogram substantially as shown in FIG.

8. 2. The crystalline form of claim 1, characterized by: (i) a powder X-ray diffraction pattern (CuKα) measured at room temperature comprising 2θ values ​​(in degrees) at 9.0±0.2, 11.3±0.2, 15.2±0.2, and 21.1±0.2; and (ii) a differential scanning calorimetry (DSC) thermogram substantially as shown in FIG.

2.

9. 10. The crystalline form of claim 1, characterized by a mass increase of less than about 0.1% upon exposure to an increase in relative humidity from about 5% to about 95%.

10. 10. The crystalline form of claim 1, characterized by a thermogravimetric analysis plot comprising less than about 0.1% mass loss upon heating from about 30° C. to about 150° C.

11. 2. The crystalline form of claim 1, wherein said Form E is a substantially pure form.

12. 2. The crystalline form of claim 1, characterized by an observed powder X-ray diffraction pattern substantially as shown in FIG.

13. 6-(cyclopropanecarboxamido)-4-((2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)phenyl)amino)-N-(methyl-d 3 )pyridazine-3-carboxamide, 3 2.) A composition, wherein at least 90% by weight of the pyridazine-3-carboxamide is crystalline form E.

14. The 6-(cyclopropanecarboxamido)-4-((2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)phenyl)amino)-N-(methyl-d 3 14. The composition of claim 13, wherein at least 95% by weight of the pyridazine-3-carboxamide is crystalline form E.

15. Crystalline 6-(cyclopropanecarboxamido)-4-((2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)phenyl)amino)-N-(methyl-d 3 A composition comprising crystalline 6-(cyclopropanecarboxamide)-4-((2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)phenyl)amino)-N-(methyl-d 3 2.) A composition, wherein at least 95% by weight of the pyridazine-3-carboxamide is crystalline form E.

16. 6-(cyclopropanecarboxamido)-4-((2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)phenyl)amino)-N-(methyl-d 3 )pyridazine-3-carboxamide, 3 2.) A composition wherein pyridazine-3-carboxamide consists essentially of crystalline form E.

17. A pharmaceutical composition comprising the crystalline form of any one of claims 1 to 12 and a pharma- ceutically acceptable carrier or diluent.

18. 6-(cyclopropanecarboxamido)-4-((2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)phenyl)amino)-N-(methyl-d 3 2.) A pharmaceutical composition comprising crystalline form E of pyridazine-3-carboxamide and a pharma- ceutically acceptable carrier or diluent, wherein said crystalline form E is characterized by a powder X-ray diffraction pattern (CuKα) comprising 2θ values ​​(in degrees) at 9.0±0.2 and 11.3±0.2 when measured at room temperature.

19. Amorphous 6-(cyclopropanecarboxamido)-4-((2-methoxy-3-(1-methyl-1H-1,2,4-triazol-3-yl)phenyl)amino)-N-(methyl-d 3 13.) Use of the crystalline form according to any one of claims 1 to 12 in a process for the preparation of pyridazine-3-carboxamide.

20. 17. The composition of any one of claims 13-16, wherein the crystalline form E is characterized by a powder X-ray diffraction (PXRD) pattern (CuKα) comprising three or more 2θ values ​​(in degrees) selected from 9.0±0.2, 11.3±0.2, 15.2±0.2, and 21.1±0.2, wherein the PXRD pattern of the crystalline form is measured at room temperature.

21. 17. The composition of any one of claims 13 to 16, wherein the crystalline form E is characterized by an observed powder X-ray diffraction pattern substantially as shown in Figure 1.

22. The crystalline form E has the following values: a=10.41±0.10Å b=12.65±0.10Å c=15.70±0.10Å α=90.0° β=103.5±1.0° γ=90.0° Space group: P2 1 / n Number of molecules per unit cell (Z): 4 and characterized by unit cell parameters substantially equal to The composition of any one of claims 13 to 16, wherein the unit cell parameters are measured at a temperature of about 100K.